The internationalization of Chinese scholarly journals based on publications deriving from the G8 countries - Yuan, Yuan; Zhao, Yuan; Chen, Rui; Shen, Wangbing; Zhao, Rongjun (Malaysian Journal of Library and Information Science, 2021)
China’s rapid rise in international collaboration and scientific research has been widely documented, but the progress of Chinese scholarly journals towards internationalization has been less investigated. This study examines the internationality of Chinese scholarly journals using bibliometric analysis of publications deriving from the eight highly industrialized countries (the Group of 8, or G8) namely, Canada, France, Germany, Italy, Japan, Russia, the UK and the USA, from 1979 to 2016 based on the databases of the Chinese National Knowledge Infrastructure (CNKI). Annual production and research trends, research affiliations, research emphases and foci, and common journal sources were analyzed. The analysis reveals that the internationality of Chinese scholarly journals has been continuously growing since 1979 and increased rapidly from 2004 to 2010. Both foreign researchers’ submissions and internationally co-authored Chinese publications substantially contributed to the internationalization of Chinese scholarly journals. This internationalization was also influenced by the academic scopes, journal titles and disciplinary categories of Chinese journals. The potential implications and limitations of this study are discussed